Improvement of climacteric symptoms with a novel sublingual product containing trans-resveratrol - Milia, R (Progress in Nutrition, 2015)
Objectives: To assess the improvement of climacteric symptoms, especially hot flushes, evaluated analyzing the total score of Menopause Rating Scale, after supplementation with a new sublingual spray formulation of resveratrol (Talitha® PH&T SpA) able to bypass gastro-enteric tract entering directly the systemic circulation. Materials and Methods: 30 women with symptoms suggestive of climacteric syndrome present for at least one month, with or without associated amenorrhea, and evaluated according to the standardized Menopause Rating Scale (MRS) were enrolled in an open, uncontrolled study. The Sublingual Spray was administered: 4 puffs 2 times/day for 3 months. Results: Menopause Rating Scale total score: this reduction was statistically significant at 0.01 level. Hot flushes mean score: this reduction was statistically significant at the 0.01 level. MRS Single items total score: the following items showed a statistically significant reduction (p